INOVASI SOSIAL PADA PROGRAM SAHABAT PERTAMINA DI PT PERTAMINA EP SUKOWATI - Ahmad Sholikin; Moh. Hudi (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
This paper discusses social innovation in the implementation of the Sahabat Pertamina Program at PT Pertamina EP Sukowati. The program aims to improve the welfare of the surrounding community through innovative approaches. Through this research, we explore various aspects of social innovation embodied in the program, including implementation strategies, impact on the community, and involvement of relevant parties. The research methodology involved both qualitative and quantitative data analysis to gain a holistic understanding of the effectiveness of social innovation in achieving sustainable development goals. The findings of this study can provide valuable insights for practitioners, researchers, and related parties in the development of similar programs and enrich the literature on social innovation in the context of energy companies.